PS2:32 Cd64, fc gamma r i expression levels on monocyte (mcd64) as a potential biomarker for neuropsychiatric systemic lupus erythematosus (npsle). (21st March 2018) - Tsuji, S; Kikuchi-Taura, A; Oguro, E; Okita, Y; Kuzuya, K; Matsuoka, H; Teshigawara, S; Yoshimura, M; Harada, Y; Matsushita, M; Ohshima, S; Saeki, Y
Abstract : Background and purpose: Interferons (IFN), such as IFNα and IFNγ, are known to play a pivotal role for the pathogenesis of neuropsychiatric systemic lupus erythematosus (NPSLE). These IFNs enhance the expression of mCD64. We recently have reported a tight correlation between mCD64 expression levels and SLE disease activity index (SLEDAI) (r=0.68, p<0.001) (Lupus 24(10):1076–80, 2015) and shown that mCD64 expression is a simple and useful biomarker for evaluating disease activity in SLE patients. Although neuropsychiatric manifestations are critical to the management of SLE, there have been no precise and convenient biomarkers assessing the activity of NPSLE. In this study, we investigated the utility of mCD64 expression as a biomarker for NPSLE. Method mCD64 expression levels were assessed quantitatively by using flow cytometry in five patients with NPSLE. The mCD64 expression levels were compared with SLEDAI and other conventional SLE activity markers, such as anti-dsDNA antibody, complements and cerebrospinal fluid (CSF) IL-6. Result: The NPSLE events included three headaches, two aseptic meningitis and one acute confusion. At the active phase of these NPSLE events, mCD64 expressions were significantly enhanced at the median of 38 541 (range 31, 693–73, 287) molecules/cell compared to the treated inactive phase. Additionally, mCD64 expression was significantly higher in CSF IL-6 high (more than 4.3 pg/ml) group than the low group (p=0.011). The mCD64 expression levels were significantly decreased at the inactive phase of the NPSLE after treatment (p=0.027) shown in figure 1. The changes of mCD64 expression levels correlated with SLEDAI (r=0.74, p=0.014). Conclusions mCD64 expression may be a potential biomarker for evaluating not only the disease activity but also the response of treatment in NPSLE.